2016
DOI: 10.1007/s11295-016-1038-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of frost hardiness in Juglans regia L. and relationship with growth and phenology

Abstract: The growing interest in broadleaf timber plantations in the Mediterranean area has promoted several studies focusing on the identification and characterization of variability sources in main timber-producing species. J. regia is one of these species, well-adapted to this area, but with freezing, damages registrations. Breeding focused on productive traits should include knowledge of adaptation, required to obtain a good selection capable of producing a suitable turnover in timber plantations. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In walnut trees, significant genotypic effect has been observed for eco-dormancy release and cold deacclimation (Charrier et al, 2011). Calibrating such a model on different walnut genotypes would bring new perspectives in identifying the variability in carbon metabolism related iso-enzymes and unraveling the genetic basis in frost hardiness variability (Guàrdia et al, 2016; Charrier et al, 2018). This could help the breeder for genetic analysis, especially when current production areas are expected to shift due to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…In walnut trees, significant genotypic effect has been observed for eco-dormancy release and cold deacclimation (Charrier et al, 2011). Calibrating such a model on different walnut genotypes would bring new perspectives in identifying the variability in carbon metabolism related iso-enzymes and unraveling the genetic basis in frost hardiness variability (Guàrdia et al, 2016; Charrier et al, 2018). This could help the breeder for genetic analysis, especially when current production areas are expected to shift due to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…They must also be well adapted to French climatic conditions, specifically winter hardiness so with late bud break to avoid late spring frosts but also with rapid fruit development. A team of INRA Clermont-Ferrand has been working on winter hardiness and found that the high heritability of autumn and winter hardinesses, and the lack of correlation with growth traits, may provide interesting selection pathways (Guàrdia et al 2016). However, the development of dedicated models highlighted that early frost damages, although lower than at other times of the leafless period, would negatively influence fruit yield in the following year (Charrier et al 2017).…”
Section: California Breeding Programmentioning
confidence: 99%
“…Under extended warm conditions during autumn, frost damages may be critical (Guàrdia et al . , ). Frost hardening, which is tightly connected to chilling exposure, may be subsequently delayed until the moment of first freezing event (Kalberer et al ; Arora & Taulavuori ).…”
Section: Discussionmentioning
confidence: 99%
“…Autumn period with warmer conditions therefore deserve a particular attention in upcoming studies (Charrier & Améglio ; Guàrdia et al . , ).…”
Section: Discussionmentioning
confidence: 99%